(untitled) (Journal of Health, Technology and Science (JHTS), 2023)
This study aims to identify the corticosteroids in whitening cosmetic preparations circulating in Gorontalo City. The method used in this study was thin layer chromatography (TLC), with a qualitative approach and a descriptive (observational) type of research. The results showed that identification in the UV laboratory at a wavelength of 254 nm showed that from the 5 cream samples and 5 lotion samples for whitening cosmetic preparations tested, four of them were positive for the strong drug class of corticosteroid betamethasone valerate, namely with an Rf value on (cream sample E 0, 91), (lotion sample A 0, 91), (lotion sample B 1.0), and (lotion sample C 1.0) and have Rf values identical or similar to standard Rf values under the same chromatographic conditions.